2009
DOI: 10.1002/ijc.24597
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with a P53 synthetic long peptide vaccine induces P53‐specific immune responses in ovarian cancer patients, a phase II trial

Abstract: The prognosis of ovarian cancer, the primary cause of death from gynecological malignancies, has only modestly improved over the last decades. Immunotherapy is one of the new treatment modalities explored for this disease. To investigate safety, tolerability, immunogenicity and obtain an impression of clinical activity of a p53 synthetic long peptide (p53‐SLP) vaccine, twenty patients with recurrent elevation of CA‐125 were included, eighteen of whom were immunized 4 times with 10 overlapping p53‐SLP in Montan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 45 publications
4
98
0
1
Order By: Relevance
“…We have previously shown that it is possible to isolate p53-specific CD4þ T cells from the TIL of patients with ovarian cancer. 23 Furthermore both p53-specific CD4þ and CD8þ T cells can be isolated from the vaccine site in our studies on p53 vaccination. 22 Although the existence of HPV16-specific regulatory T cells is reported, there is no evidence for the existence of p53-specific regulatory T cells.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We have previously shown that it is possible to isolate p53-specific CD4þ T cells from the TIL of patients with ovarian cancer. 23 Furthermore both p53-specific CD4þ and CD8þ T cells can be isolated from the vaccine site in our studies on p53 vaccination. 22 Although the existence of HPV16-specific regulatory T cells is reported, there is no evidence for the existence of p53-specific regulatory T cells.…”
Section: Discussionmentioning
confidence: 93%
“…[18][19][20] Similar vaccine approaches are tested for the treatment of p53-overexpressing cancers. [21][22][23] There is a strong notion that the presence and type of preexisting circulating and local tumor-specific immunity influences the clinical outcome as well as that of immunotherapeutic approaches. 6,18 Thus, to optimize immune resistance to HNSCC, a better understanding of the character and specificity of tumor-infiltrating-lymphocytes (TIL) in HNSCC is needed.…”
mentioning
confidence: 99%
“…32 The vaccine was generally well-tolerated and was successful in inducing p53-specific, Th2-dominant T cell responses in patients who received all four vaccinations. However, clinical response did not correlate with vaccine-mediated immunity.…”
Section: Cancer Immunotherapymentioning
confidence: 94%
“…Long peptides do not bind to HLA directly and only professional APCs, such as DCs, can take it up [76] . However, it was reported that some long peptides might induce peptide-specific regulatory T cells (Tregs) and Th2 cells to limit the clinical efficacy of long peptides [77,78] . On the other hand, in DC vaccine therapy, peptides are pulsed on mature DCs ex vivo and they cannot be loaded on unprofessional APCs.…”
Section: Vaccine Pulsed With Peptidesmentioning
confidence: 99%